Soy Isoflavone Mediated Modulation of IL-1β Related Inflammatory Pathways in Oral Mucosal Cells: A Scoping Review of Experimental Studies - Nuroh Najmi; Faisal Kuswandani; Anggun Rafisa; Felisha Febriane Balafif (Jurnal EduHealth, 2025)
Background: Soy isoflavones, particularly genistein, have been widely studied for their anti-inflammatory properties. However, evidence regarding their modulatory effects on interleukin-1β (IL-1β)–related inflammatory pathways in oral mucosal tissues remains limited. Objective: This scoping review aimed to map the available experimental evidence on the effects of genistein on inflammatory responses associated with IL-1β in the oral cavity. Methods: A scoping review was conducted following a comprehensive literature search of PubMed and ScienceDirect databases. Articles published in English between 2016 and 2026 were screened using predefined keywords related to soy isoflavones, genistein, IL-1β, inflammation, and oral or periodontal tissues. Original experimental studies focusing on inflammatory modulation in oral or periodontal contexts were included. Results: From the literature search, only one experimental study met the inclusion criteria. The included study investigated a genistein-loaded folic acid–modified liposome-hydrogel composite for periodontitis treatment. The findings demonstrated that genistein exerted anti-inflammatory effects by modulating inflammatory cytokines, including IL-1β, and inhibiting the TLR4/MyD88/NF-κB signaling pathway. The study also reported improved inflammatory regulation through macrophage phenotype modulation and interaction with periodontal ligament stem cells. Conclusion: Current experimental evidence on the role of genistein in modulating IL-1β–related inflammation in the oral cavity is scarce. The limited findings suggest that genistein has potential anti-inflammatory effects in periodontal inflammation; however, further well-designed experimental studies focusing specifically on oral mucosal cells and inflammatory pathways are needed to support its therapeutic application.